2005
DOI: 10.1016/j.str.2004.11.006
|View full text |Cite
|
Sign up to set email alerts
|

A Vinculin Binding Domain from the Talin Rod Unfolds to Form a Complex with the Vinculin Head

Abstract: The cytoskeletal protein talin plays a key role in activating integrins and in coupling them to the actin cytoskeleton. Its N-terminal globular head, which binds beta integrins, is linked to an extended rod having a C-terminal actin binding site and several vinculin binding sites (VBSs). The NMR structure of residues 755-889 of the rod (containing a VBS) is shown to be an amphipathic four-helix bundle with a left-handed topology. A talin peptide corresponding to the VBS binds the vinculin head; the X-ray cryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
162
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(176 citation statements)
references
References 50 publications
10
162
0
1
Order By: Relevance
“…However, in contrast to the VBS sites that each correspond to hydrophobic residues exposed on one side of an amphipathic ␣-helix of the talin rod domain (17)(18)(19), our previously reported results (1) suggested that the highly conserved and charged residues clustered on the solvent face of the amphipathic talin rod ␣-helix 50 might be involved in the helix-helix interaction of IBS2 with ␤3. The sequence alignment of human talin helix 50 with the equivalent talin sequence of other species ranging from mouse to zebrafish is shown in Fig.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…However, in contrast to the VBS sites that each correspond to hydrophobic residues exposed on one side of an amphipathic ␣-helix of the talin rod domain (17)(18)(19), our previously reported results (1) suggested that the highly conserved and charged residues clustered on the solvent face of the amphipathic talin rod ␣-helix 50 might be involved in the helix-helix interaction of IBS2 with ␤3. The sequence alignment of human talin helix 50 with the equivalent talin sequence of other species ranging from mouse to zebrafish is shown in Fig.…”
mentioning
confidence: 69%
“…The ␣-actinin central rod domain, which is composed of 4 spectrin repeats of 3 ␣-helices (8,9), associates with integrin ␤ subunits as well as vinculin through distinct helix-helix interactions (10 -16). Also, the 3 major talin rod-vinculin head (Vh) contacts have a similar architecture based on hydrophobic helixhelix interactions (17)(18)(19). Other FA proteins, such as members of the paxillin supergene family comprising paxillin, Hic-5, leupaxin, and PaxB, rely on an ␣-helical LD motif for their interaction with cognate partners, such as FAK, ILK, vinculin, or actopaxin, and establish a helix-helix interaction characterized by a hydrophobic patch between the two helices and surrounded by basic residues on one helix that interacts with the negatively charged residues of the second helix (20).…”
mentioning
confidence: 99%
“…VBSs are defined by a single amphipathic helix of ϳ25 residues forming six turns, with the hydrophobic residues involved in vinculin binding clustered on one face of the amphipathic helix. Crystallographic and NMR structures have shown that the three major VBSs are contained within helical bundles, with the 6 key hydrophobic residues involved in vinculin binding buried within the hydrophobic core of the ␣-helical bundles (31)(32)(33). Talin binds vinculin with relatively low affinity, confirming that the majority of VBSs in talin are indeed cryptic (34).…”
Section: Discussionmentioning
confidence: 99%
“…The rod domain of talin comprises 62 amphipathic ␣-helices that are assembled into a series of ␣-helical bundles (33,34). Therefore, to avoid disrupting the tertiary structure of the resulting protein, we introduced stop codons between ␣-helical bundles as designated by arrowheads in Fig.…”
Section: Discrete Region Of Rod Domain Maintains a Cytosolic Pool Ofmentioning
confidence: 99%
“…These lipid-binding sites, which are aligned along one surface of the extended FERM domain, make extensive contacts with the plasma membrane (22) and play a critical role in integrin activation (21,26,31). The rod domain of talin consists of 62 amphipathic ␣-helices that are assembled into a series of ␣-helical bundles (33,34), and autoinhibitory interactions between THD and the rod domain regulate the functions of talin including its interactions with integrins (17,(35)(36)(37)(38)(39)(40).…”
mentioning
confidence: 99%